Avaliação do uso de ultrassom para a conversão de ácido tânico visando à obtenção de ácido gálico - Wohlmann, Wilian (2021)
Tannic acid is a macromolecule belonging to the hydrolysable tannins group, with multiple units of gallic acid linked to a central sugar. This compound is considered to have a low level of biodegradability and, under uncontrolled conditions, it can bring risks to the environment, harming human health and ecosystems. Despite the low biodegradability of tannic acid, its chemical structure is of industrial interest due to the possible oxidation generating compounds with high added value, such as gallic acid, pyrogallol and ellagic acid. In this sense, the development of alternative treatments for the recovery of this waste is an important research topic. In this work, the use of ultrasound was investigated and associated with the addition of hydrogen peroxide for tannic acid oxidation in order to produce gallic acid. Ultrasound-assisted oxidation experiments were performed using an ultrasound probe operating at 20 kHz with nominal power of 750 W. The following experimental conditions were evaluated: sonication time (10 to 45 min), reaction temperature (50 to 90 ºC), solution pH (3 to 11), H2O2 concentration (0.2 to 8.6 mol L-¹), gas addition (Ar, O2 and compressed air), probe type (10 to 25 mm in diameter), ultrasound amplitude (20 to 70%), tannic acid concentration (170 to 1360 mg L-¹) and application of pulsed ultrasound (cycles of 10 to 60 s). For all evaluated conditions, the gallic acid concentration was quantified by ultra performance liquid chromatography coupled to time-of-flight mass spectrometry and electrospray ionization (UPLC-ESI-ToF-MS). After separation and isolation, the gallic acid structure was confirmed by nuclear magnetic resonance of hydrogen and carbon (¹H and ¹³C NMR). It is important to emphasize that this study was developed as a proof of concept to demonstrate the potential of ultrasound for the conversion of tannic acid to gallic acid using only diluted H2O2 as a reagent. After the optimization of the experimental conditions, using an ultrasound probe operating at 20 kHz with 50% of amplitude and 750 W of nominal power, the yield of the gallic acid production was 128 ± 4 mg g-¹ of tannic acid (using an initial concentration of 170 mg L-¹ of tannic acid). The total reaction time was set at 30 min with the addition of H2O2 at a concentration of 1 mol L-¹ and reaction temperature of 90 ºC. Under conditions using mechanical agitation (100 to 1000 rpm), the gallic acid production was reduced by at least 50% (less than 78 ± 4 mg g-¹ of tannic acid). The proposed process made possible the tannic acid valorization in a product with high added value used in several processes in chemical industry.